2014
DOI: 10.4103/0189-6725.129210
|View full text |Cite
|
Sign up to set email alerts
|

Lipoblastoma in childhood: About 10 cases

Abstract: It is important to consider lipoblastoma in the diagnosis of a rapidly enlarging fatty mass in children. Complete resection is the only definitive treatment and should not be delayed when impingement on surrounding structures is imminent. There is a tendency for these lesions to recur despite presumed complete excision. Therefore, follow-up for a minimum of 5 years is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 9 publications
0
20
1
5
Order By: Relevance
“…The long‐term prognosis of patients with lipoblastoma, even recurrent tumors, remains excellent. There has been no evidence of malignant degeneration in the literature to date, but local recurrence remains a concern, with rates quoted as 12%–25% in some limited small case series and reports . Interestingly, most recurrences have been noted to occur within 2 years of resection, which is in stark contrast to our patient, who presented almost 17 years later .…”
Section: Discussioncontrasting
confidence: 71%
“…The long‐term prognosis of patients with lipoblastoma, even recurrent tumors, remains excellent. There has been no evidence of malignant degeneration in the literature to date, but local recurrence remains a concern, with rates quoted as 12%–25% in some limited small case series and reports . Interestingly, most recurrences have been noted to occur within 2 years of resection, which is in stark contrast to our patient, who presented almost 17 years later .…”
Section: Discussioncontrasting
confidence: 71%
“…There is a slight male predominance, with a male:female ratio of 1.7:1. Clinically, lipoblastoma most commonly presents as a painless subcutaneous soft tissue mass that steadily increases in size , as demonstrated in patient 1, although it has also been reported to mimic vascular tumors such as infantile hemangiomas , as demonstrated in patient 2. In contrast, the clinical appearance of the lipoblastoma in patient 3 more closely resembled a myofibroma or hamartoma.…”
Section: Discussionmentioning
confidence: 98%
“…Lipoblastoma occurs almost exclusively during infancy, childhood, and adolescence. Our review of the literature included 263 cases of lipoblastoma, with a median age at presentation of 22.6 months (Table ) . There is a slight male predominance, with a male:female ratio of 1.7:1.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions are usually noted during the first three years of life and are most commonly painless nodules or masses found on the upper and lower extremities (2). Omental lipoblastoma is extremely rare; only 12 cases of omental lipoblastoma have been reported in the English literature (3)(4)(5)(6)(7)(8). With regard to differentiation between lipomas and lipoblastomas, lipomas are rare during the first two decades of life, and unlike lipoblastomas, they are rarely larger than 10 cm (2).…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the primary treatment for lipoblastoma is complete resection. The local recurrence rate is reported to be between 14% and 25% (8). In contrast, Mahour et al suggested that if a child with lipoblastoma is followed up long enough, the tumor will eventually differentiate into a mature lipoma (10).…”
Section: Discussionmentioning
confidence: 99%